Employee achievement orientations and personality as predictors of job satisfaction facets. (April 2015) - Avery, Rachel E.; Smillie, Luke D.; Fife-Schaw, Chris R.
Highlights: Extraversion relates to expectation-based-job-satisfaction. Neuroticism and Mastery-Approach relate to satisfaction-with-own-job-performance. Mastery-Approach accounts for unique variance in satisfaction-with-own-job-performance. Experiences of satisfaction at work can be traced to stable approach competence specific motivational tendencies. Abstract: This paper examines the incremental value of achievement orientations (Mastery-Approach; Mastery-Avoid; Performance-Approach; Performance-Avoid), above Extraversion and Neuroticism, in predicting two different types of satisfaction outcomes; expectation-based-job-satisfaction (EX-JS) and satisfaction-with-one's-own-job-performance (P-JS). Using structural equation modelling, data from 242 UK government body employees showed that only Extraversion shared a (positive) relationship with EX-JS. Whereas, the strongest relations with P-JS were found for Neuroticism and Mastery-Approach with both sharing positive relationships with this satisfaction outcome. Analyses indicated that Mastery-Approach accounted for unique variance in P-JS beyond Extraversion and Neuroticism. Findings show that there is scope for experiences of satisfaction at work to be traced to stable approach competence specific motivational tendencies.